Evaluation of leap motion control for hand rehabilitation in burn patients: An experience in the dust explosion disaster in Formosa Fun Coast. Issue 1 (February 2019) - Wu, Yah-Ting; Chen, Kuo-Hu; Ban, Shiun-Lei; Tung, Kwang-Yi; Chen, Li-Ru
Abstract: Hand burns cause functional impairment. Leap motion control (LMC), a kind of virtual reality games, employs a novel system that provides biofeedback and training of fine motor function and functional skills. In this study, we hypothesized that LMC would improve burned hand function. Sixteen participants were allocated to either the LMC group or the control group. The LMC group played 20 min identical leap motion video games after 40 min traditional occupational therapy (OT). The control group received traditional OT for 60 min. Both groups received interventions 2 days a week for 4 months. A series of questionnaires were administered, including BSHS-B, QuickDASH, iADL, and Barthel index. Data on baseline characteristics including joint range of motion (ROM), grip and pinch strength, and scar thickness were obtained. Furthermore, we used the Mann–Whitney U test and Wilcoxon signed-rank test for comparison, as appropriate. We found improvements in BSHS-B, QuickDASH, and iADL in the LMC group (all p < 0.05) compared to those in the control group. In the LMC-trained hand, the ROM of the thumb IP joint and pinch strength increased, whereas the scar thickness over the first dorsal interossei muscle decreased ( p < 0.05). In conclusion, leap motion training could help patients with hand burns to increase finger ROM, decrease scar thickness, and improve hand function.